2023
DOI: 10.1101/2023.05.09.540038
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequence-Dependent Material Properties of Biomolecular Condensates and their Relation to Dilute Phase Conformations

Abstract: Material properties of phase-separated biomolecular assemblies, enriched with disordered proteins, dictate their ability to participate in many cellular functions. Despite the significant effort dedicated to understanding how the sequence of the disordered protein drives its phase separation to form condensates, little is known about the sequence determinants of condensate material properties. Here, we decipher these relationships for charged disordered proteins using model sequences comprised of glutamic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 113 publications
(304 reference statements)
1
4
0
Order By: Relevance
“…In a single-component brush, more evenly shuffling the NFM sequence charges caused the brush to expand further. This finding in the context of surface-tethered IDPs complements evidence from IDPs free in solution 32,3436 and even specifically NFM tail fragments in solution 37 , where sequence charge desegregation tends to cause chain expansion. We observe that the charge shuffle effect on NFM tail brush height is negligible at low ionic strengths, possibly due to the lack of screening of significant charge repulsion between distant residues in the net-negative NFM sequence.…”
Section: Discussionsupporting
confidence: 71%
“…In a single-component brush, more evenly shuffling the NFM sequence charges caused the brush to expand further. This finding in the context of surface-tethered IDPs complements evidence from IDPs free in solution 32,3436 and even specifically NFM tail fragments in solution 37 , where sequence charge desegregation tends to cause chain expansion. We observe that the charge shuffle effect on NFM tail brush height is negligible at low ionic strengths, possibly due to the lack of screening of significant charge repulsion between distant residues in the net-negative NFM sequence.…”
Section: Discussionsupporting
confidence: 71%
“…This would suggest that FUS LC wildtype and LAF-1 RGG interactions are weakly attractive under experimental conditions, as EI close to 1 is observed, unlike partitioning of synthetic polymers such as PEG in aqueous two-phase systems in which EI << 1 63, 64 . Elevated concentrations of B at the interface for non-zero λ AB reflect locally enhanced concentration of client molecules due to favorable heterotypic interactions, which are not sufficiently strong to cause co-mixing but may be sufficient to alter condensates’ material properties and composition control via a thin interfacial layer 6568 .…”
Section: Resultsmentioning
confidence: 99%
“…Intrinsically disordered proteins (IDPs) play an important role in the formation of biomolecular condensates through LLPS [6][7][8][9][10][11] . Due to the numerous similarities between IDPs and synthetic polymers, classical polymer-based models offer a powerful approach for investigating the conformations 12 , dynamics 13 , and phase behavior of IDPs [14][15][16][17] . In particular, such models have been extensively used to reveal the sequence-dependent conformations of IDPs in the dense and dilute phases of condensates [18][19][20][21][22][23][24][25][26][27] .…”
mentioning
confidence: 99%
“…Lipiński et al reported that the condensate interface can serve as a nucleation site promoting the aggregation of amyloidogenic proteins 31 . Inspired by the critical role of interfaces in various functionalities, much research has focused on determining mesoscopic interfacial properties such as surface tension 13,32,33 , surface adsorption 34 , and electrochemical properties 35 , which are deemed important for regulating biological functions 29,36 . For example, it was shown that the condensates could form an autophagosome only if the surface tension is lower than a critical value 37 .…”
mentioning
confidence: 99%